The Singing Troubadour of the Hiawatha Valley: the Life and Radio Career of Ronnie Owens, the Singing Cowboy of Red Wing, Minnesota - (:unkn) unknown (My University, 2014)
The number of local, rural radio stations grew dramatically at the aftermath of World War II. These stations modeled their programming on that of large, urban radio stations while providing local news and music and entertainment by local musicians and performers. One such performer found on radio stations throughout America was the character of the singing cowboy, originating from paperback novels and the silver screen. Little research has been conducted on the singing cowboy on local radio stations however. In this thesis, I will provide a model on how to examine the singing cowboy on a local radio station. More specifically, I will examine the life and career of Ronnie Owens and his radio career on the rural radio station, KAAA, in Red Wing, Minnesota.
Keywords: American Music; Local Radio; Minnesota; Radio History; Singing Cowboy; Western Folk